Hungarian Monitoring, 12 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev's Siberian visit - Polish intellectuals and the forthcoming roundtable discussions Domestic Affairs: - Demonstrations against Gabčíkovo-Nagymaros dam in Budapest and Szeged - Pro-reform evenings - Debate on the right to assemble and associate - Budapest Council discusses current investments - Economists' traveling meeting in Gyula - Hungarian cultural delegation departs for Seoul Külpolitika: - Gorbacsov szibériai látogatása - A lengyel értelmiség és a közelgő kerekasztal-tárgyalások Belpolitika: - A Bős-nagymarosi vízlépcsőt ellenzők demonstrációja Budapesten és Szegeden - Reformpárti Esték - Vita az egyesülési és gyülekezési jogról - A Fővárosi Tanács a folyamatban levő beruházásokról tanácskozott - Közgazdász vándorgyűlés Gyulán - Magyar kulturális delegáció indul Szöulba